2004
DOI: 10.1159/000084565
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of Combined Tet Repressor Mutants for Effector and Operator Recognition and Allostery

Abstract: Tet repressor mutants with a shifted effector specificity, preference for a mutant operator sequence or reversion of activity were combined to construct variants bearing two or three phenotypic alterations. TetR alleles with combinations of altered operator and effector specificities can be created by merging the respective residues in a single polypeptide. The mutations giving rise to revTetR, on the other hand, show drastic influences on the ligand binding phenotypes when combined with respective alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…TetR i2 ‐V99G is one of the best revTetR i2 variants with 4‐ddma‐atc specific repression, almost completely lacking repression with atc [9]. As the V99G exchange in the wild‐type sequence background displays no reverse phenotype and slightly increased repression in the presence of 4‐ddma‐atc, we decided to determine the contribution of each amino‐acid exchange in TetR i2 ‐V99G to the combined activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TetR i2 ‐V99G is one of the best revTetR i2 variants with 4‐ddma‐atc specific repression, almost completely lacking repression with atc [9]. As the V99G exchange in the wild‐type sequence background displays no reverse phenotype and slightly increased repression in the presence of 4‐ddma‐atc, we decided to determine the contribution of each amino‐acid exchange in TetR i2 ‐V99G to the combined activity.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of mutations resulting in 4‐ddma‐atc specificity with those yielding revTetR in the same polypeptide did not yield efficient mutants with combined activities [9]. Thus, these properties of TetR must be interrelated.…”
mentioning
confidence: 99%
“…It was recently demonstrated that the different phenotypic alterations of shifted operator and inducer preference and reverse behaviour of TetR variants can functionally be combined in novel regulators, which, e.g. only in the presence of 4‐de‐dimethylamino‐atc bind to tetO (Bertram et al. , 2004; Henssler et al.…”
Section: Modifications Of Tet Regulation: Revtetr and Tetr Mutants Emmentioning
confidence: 99%
“…It was recently demonstrated that the different phenotypic alterations of shifted operator and inducer preference and reverse behaviour of TetR variants can functionally be combined in novel regulators, which, e.g. only in the presence of 4-de-dimethylamino-atc bind to tetO (Bertram et al, 2004;Henssler et al, 2005). A dodecapeptide, termed Tip (transcription-inducing peptide), isolated by phage display has pronounced inducing capacities for TetR(B) (Klotzsche et al, 2005).…”
Section: Modifications Of Tet Regulation: Revtetr and Tetr Mutants Emmentioning
confidence: 99%
“…Traditional small-molecule-inducible expression systems, such as those derived from the lactose (lac), arabinose (ara) and tetracycline (tet) operons, have been extensively utilized for the production of recombinant proteins, [1] gene function analysis, [2] target validation, and drug discovery. [3] Inducible expression systems have also become indispensable tools in synthetic biology and have been used to control genetic circuits and networks, [4] as well as metabolic pathways for the production of pharmaceuticals, biofuels, and fine chemicals.…”
mentioning
confidence: 99%